2013
DOI: 10.1371/journal.pone.0069133
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Protein Phosphatase-1 and Aurora Protein Kinase Suppressors Reveals New Aspects of Regulatory Protein Function in Saccharomyces cerevisiae

Abstract: Protein phosphatase-1 (PP1) controls many processes in eukaryotic cells. Modulation of mitosis by reversing phosphorylation of proteins phosphorylated by aurora protein kinase is a critical function for PP1. Overexpression of the sole PP1, Glc7, in budding yeast, Saccharomyces cerevisiae, is lethal. This work shows that lethality requires the function of Glc7 regulatory proteins Sds22, Reg2, and phosphorylated Glc8. This finding shows that Glc7 overexpression induced cell death requires a specific subset of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 87 publications
1
7
0
Order By: Relevance
“…The genetic interactions annotated here support a unique function for Fpr3 in orchestrating centromeric chromatin dynamics during chromosome segregation. This is fully consistent with existing literature (Hochwagen et al 2005; Krogan et al 2006; Macqueen and Roeder 2009; Ghosh and Cannon 2013; Ohkuni et al 2014). Our comparative analysis provides additional systems-level evidence that this role is not shared with Fpr4, indicating that Fpr3, potentially as a homo-oligomer, may regulate chromatin in a way that affects chromosome segregation (Hochwagen et al 2005; Macqueen and Roeder 2009).…”
Section: Discussionsupporting
confidence: 93%
“…The genetic interactions annotated here support a unique function for Fpr3 in orchestrating centromeric chromatin dynamics during chromosome segregation. This is fully consistent with existing literature (Hochwagen et al 2005; Krogan et al 2006; Macqueen and Roeder 2009; Ghosh and Cannon 2013; Ohkuni et al 2014). Our comparative analysis provides additional systems-level evidence that this role is not shared with Fpr4, indicating that Fpr3, potentially as a homo-oligomer, may regulate chromatin in a way that affects chromosome segregation (Hochwagen et al 2005; Macqueen and Roeder 2009).…”
Section: Discussionsupporting
confidence: 93%
“…Most relevant in the context of this study, five of the identified Ssb-interactors comprise the central components of the SNF1/Glc7 signaling pathway: Snf1, Sip1 and Snf4, which form a holo-SNF1 complex, Glc7 and Reg1 (Table 1 and Figure 3D ) ( 2 , 3 ). Ssb also formed a crosslink to Sds22, an essential, however poorly characterized subunit of Glc7 ( 49 ), which also contacts Snf4 ( 50 ) and is phosphorylated by SNF1 (Yeast Kinase Interaction Database, 51 ). Employing a cleavable crosslinker, the interaction between Snf1 and Ssb was confirmed via immunoblotting (Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly to Ppz1, the overexpression of Glc7 has been revealed to be deleterious for the cell [ 34 , 35 ]. However, a number of evidences suggest that the mechanisms for toxicity are not the same [see [ 28 ] for a discussion].…”
Section: Discussionmentioning
confidence: 99%